Peningkatan Produksi Ikan Patin melalui Teknologi Hapa Ganda, Pemuasaan dan Pemberian Pakan Berprobiotik di Desa Semangat Bakti, Kecamatan Alalak, Barito Kuala, Kalimantan Selatan - Junius Akbar; Muhammad Adriani; Arisa Hernida; Halimatus Sa’diyah; Muhammad Husni; Muhammad Maulana; Gusti Muhammad Furqon Syabani (I-Com: Indonesian Community Journal, 2024)
The Jaya Bakti fish cultivator group (pokdakan) as the partner's target audience is one of the pokdakan in Alalak sub-district. Pokdakan Jaya Bakti carries out catfish (Pangasius sp) and catfish (Clarias sp) cultivation activities. Fish production is still low due to limited technical knowledge of fish cultivation and the high mortality rate of catfish fry measuring 1-3 cm. The aim of Community Service (PKM) activities is to introduce double hapa technology as a seed incubator and satisfaction applications. The output target of this PKM activity is to increase the survival rate of catfish seeds by >70% and reduce feed production costs by 20-30%. The method of implementing PKM activities is through counseling, demonstration and evaluation methods. The results of the evaluation showed that the knowledge of the partner's target audience was found on average not to know a little (X = 18.33), after being given counseling, the level of knowledge of the partner's target audience changed to enough to know a lot about double hapa technology as a fish seed incubator and satisfaction applications (Y = 36.6). The results of the two-party test analysis showed a significant increase where t hit = 7.64 > t tab (0.05) = 2.13 and t tab (0.01) = 2.95. This means that there is an increase in knowledge after the counseling is carried out. From this PKM activity, the partner target audience has a supportive attitude towards the activities carried out, shown by the enthusiastic involvement of the partner’s target audience in this PKM program.